Penerapan model pembelajaran means ends analysis (MEA) untuk meningkatkan kemampuan menganalisis materi FPB dan KPK pada peserta didik kelas IV sekolah dasar - Miftakhul Jannati; Siti Kamsiyati; Anesa Surya (Didaktika Dwija Indria, 2020)
Improving the ability to analyze the FPB and KPK by applying Means Ends Analysis model is the purpose of this research. This research is Classroom Action Research with two cycles. Students of the 4th students at SD Ta’mirul Islam Surakarta in the 2019/2020, totalling 24 students is the subject. Data collection techniques in the form of interview, observation, test, and document analysis. Data analysis are source and technique triangulation, and content validity. Analysis of the data used is the Miles-Huberman interactive analysis model. The initial conditions of analysis ability of 4 th students showed 37,5%. The cycle I at the first meeting resulting in a percentage of 75%, the second meeting is 66.67%. The cycle II at the first meeting producing a percentage of 87.5%, the second meeting is 91.67%. Based on the result of the research, it can be conclude that the ability to analyze FPB dan KPK on 4 th students of SD Ta’mirul Islam in the 2019/2020 can be improved through the Means Ends Analysis model. This research contributed to be used as a reference and be a development in varied learning activities in mathematics subject.